"Mission impossible"? how a successful female cross-country skier managed a dual career as a professional athlete and medical student - Bergström, M.; Solli, G. S.; Sandbakk, Ø.; Sæthe, S. A. (Scandinavian Sport Studies Forum, 2022)
The aim of the present case study is to illuminate the factors contributing to the initiation, maintenance and discontinuation of the dual career of a Norwegian world-class athlete and medicine student. We additionally aimed to highlight contextual factors facilitating and impeding the dual career development. The participant Astrid Uhrenholdt Jacobsen was a Norwegian student-athlete in the 2005-2020 period when she concurrently achieved 10 FIS World Championship medals, one Olympic medal, and 43 World Cup podiums in cross-country ski- ing. Day-to-day training diary data, study load and progress, performance, and interviews were analysed. In most years, the participant`s annual training vol- ume was c. 800-900 hrs/year. No significant differences in athletic performance were seen between the years with full-time studies, part-time studies, and study breaks. The participant Jacobsen experienced conflicting schedules and a lack of dual career support from stakeholders as the major challenges. Hence, the present single-case study provides unique data on the process and management of a dual career.